Effects of copper and vermicompost on growth and yield of cowpea (Vigna unguiculata L.) Walp and nutrient accumulation in its fruits - Sharif, AT; Ali, AHMZ; Rahman, MK (Journal of Biodiversity Conservation and Bioresource Management, 2020)
The effects of copper (Cu) and vermicompost (VC) on growth and yield of cowpea (Vigna unguiculata L.) Walp and nutrient accumulation in its fruits was examined. Eight treatments of Cu and VC were used. The highest plant height (226.67 cm), leaf number per plant (86.33), leaf area (174.12 cm2/plant), dry weight (13.98 g/plant), fruit length (52.4 cm), fruit number per plant (6), and fruit yield (5.65 g/plant) were recorded in Cu0.5 kg/ha + VC5 ton/ha treatment at harvest. The results of growth and yield of cowpea varied significantly (p≤ 0.05) and increased with time. The total nutrient concentrations in the fruits were measured and varied significantly (p≤ 0.05). The highest concentration of total P (0.79%), K (4.14%), S (0.42%), Cu (27 mg/kg), Fe (640 mg/kg) and Mn (59 mg/kg) in the fruits were observed in Cu0.5 kg/ha + VC5 ton/ha treatment and total N (4.29%) and Zn (88 mg/kg) were found in Cu1.5 kg/ha + VC5 ton/ha treatment. The overall best growth, yield and nutrient accumulation in the fruits of cowpea were achieved in Cu0.5 kg/ha + VC5 treatment. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 13-18